The mechanism of the force enhancement by MgADP under simulated ischaemic conditions in rat cardiac myocytes - Papp, Zoltán (Blackwell Science Inc, 2002)
In this study, the effects of MgADP and/or MgATP on the Ca(2+)-dependent and Ca(2+)-independent contractile force restoration were determined in order to identify the origin of the tonic force increase (i.e. ischaemic contracture) which develops during advanced stages of ischaemia. Experiments were performed at 15 °C during simulated ischaemic conditions in Triton-skinned right ventricular myocytes from rats. In the presence of 5 mm MgATP the maximal Ca(2+)-dependent force (P(o)) of 39 ± 2 kN m(−2) (mean ± s.e.m.) under control conditions (pH 7.0, 15 mm phosphocreatine (CP)) decreased to 8 ± 1 % during simulated ischaemia (pH 6.2, 30 mm inorganic phosphate (P(i)), without CP). This change was accompanied by a major reduction in Ca(2+) sensitivity (pCa(50) 4.10 vs. 5.62). Substitution of MgADP for MgATP restored isometric force production and its Ca(2+) sensitivity (pCa(50) 4.74 at 4 mm MgADP and 1 mm MgATP). In addition, it shifted the MgATP threshold concentration of Ca(2+)-independent force development to higher levels in a concentration-dependent manner. However, Ca(2+)-independent force was facilitated less by MgADP than Ca(2+)-dependent force. The MgADP-induced increase in force was accompanied by marked reductions in the velocity of unloaded shortening and the rate of tension redevelopment. These data and simulations using a model of cross-bridge kinetics suggest that the ischaemic force is not a consequence of a reduction in intracellular MgATP concentration, but identify MgADP as a key modulator of the cross-bridge cycle under simulated ischaemic conditions in cardiac muscle, with a much lower inhibition constant (0.012 ± 0.003 mm) than in skeletal muscle. Therefore, MgADP has a high potential to stabilize the force-generating cross-bridge state and to facilitate the development of ischaemic contracture, possibly involving a Ca(2+) activation process in the ischaemic myocardium.